Systematic literature review: Ethnomathematics research in Indonesia - Iffah, Rona Dhiya Layli; Subanti, Sri; Usodo, Budi; Nurhasanah, Farida (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Ethnomathematics research has developed globally, with significant contributions from various countries, especially from Indonesia. Indonesia has diversity and cultural richness that offers opportunities to strengthen its education system, especially in improving mathematical literacy by connecting learning materials with daily activities and cultural norms owned by students. This article presents a systematic literature review on ethnomathematics research in Indonesia. Ethnomathematics is the study of mathematical practices that grow and develop in the cultural context of local communities. This study aims to provide a clear picture of the development of ethnomathematics research in Indonesia, especially in terms of research year, research methodology, regional distribution, level of education, types of cultural products, and types of media used. This study uses a systematic literature review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) rule with data sources from ERIC and Scopus. Data was collected without the criteria of the year, with the aim of finding out when ethnomathematics began to be developed in Indonesia. Next, this study differs from previous ethnomathematics systematic literature review studies, focusing on different research scopes, data sources, and objectives. The results show that ethnomathematics emerged in Indonesia in 2016. Utilising an ethnomathematics approach can improve students' mathematical literacy in Indonesia by using more comprehensive research methods (quantitative, mix-method, R&D) and focusing on examining the cultural richness of the Javanese tribes in Central Java, East Java, and DIY, which are still underresearched and through traditional cultural products. In addition, it is hoped that ethnomathematics research can be expanded to other levels of education other than junior high school and utilise digital learning media.